P143 The effect of JAK inhibition on the metabolome of neutrophils from patients with rheumatoid arthritis. (26th April 2021) - Alarcon, Michele Fresneda; Grosman, Rudi; Chokesuwattanaskul, Susama; Phelan, Marie; Wright, Helen Louise
Abstract: Background/Aims   Janus kinase inhibitors (JAKi) including baricitinib and tofacitinib target the JAK/STAT pathway and are clinically effective in treating rheumatoid arthritis (RA). Neutrophils play a key role in the pathophysiology of RA and their function is directly affected by these drugs as shown by clinical trials of JAKi which report increased infection rates and transient neutropenia during therapy. The aim of this work is to determine difference in the metabolome of neutrophils from healthy controls and patients with RA, and the effect of JAKi on the metabolome of healthy and RA neutrophils. Methods   Neutrophils were isolated from healthy controls (HC) (n = 10) and patients with RA (n = 10 DMARD-naïve, n = 10 Biologics-naive) and pre-incubated with baricitinib, tofacitinib or a pan-JAK inhibitor (all 200ng/mL) for 2h before snap-freezing. Metabolites were extracted by 50:50 v/v AcN:H2 O and analysed by 1 H NMR spectroscopy using a 700 MHz Avance IIIHD Bruker NMR spectrometer equipped with a TCI cryoprobe. Chenomx, Bruker TopSpin and tameNMR software were used to identify metabolites and process spectra. Statistical analysis and machine learning models were implemented using R and the Mixomics package. Pathway analysis was carried out using Ingenuity (IPA). ROS production in response to 15 min fMLP stimulation was measured using DHR-123 and flow cytometry. Results   At 0h, changes in levels of NADP+, NADPH and hypoxanthine in RA neutrophils indicated increased production of ROS via NADPH oxidase and xanthine oxidase compared to HC. Lower levels of glucose and increased levels of lactic acid also suggested increased glycolysis in RA neutrophils compared to HC. However after 2h incubation with JAKi, a difference in the response to these drugs was observed. 80 metabolites were higher in RA neutrophils compared to HC following 2h JAKi treatment. IPA analysis revealed the metabolites higher in RA neutrophils were involved in NAD biosynthesis, NAD phosphorylation/dephosphorylation, amino acid synthesis and transport, and carbohydrate metabolism. Changes in the levels of NADP+, NADPH and hypoxanthine in RA neutrophils indicate that JAKi inhibit ROS production. We therefore confirmed experimentally that JAKi inhibit ROS production in response to fMLP (p < 0.05). IPA also predicted altered neutrophil cell functions including cell death and cell-to-cell signalling. We previously showed that JAKi did not affect the constitutive rate of neutrophil apoptosis, however JAKi significantly inhibit the delay in apoptosis induced by GM-CSF (p < 0.05). No significant difference in the metabolome was observed when comparing tofacinib-treatment and baricitinib-treatment in either the HC or RA patient group. Conclusion   The metabolome of RA and HC neutrophils is different at baseline. JAKi alter the levels of intracellular metabolites involved in neutrophil activation and ROS production in RA. This may explain, in part, the efficacy of JAKi in decreasing disease activity and joint damage in RA. Disclosure   M. Fresneda Alarcon: None. R. Grosman: None. S. Chokesuwattanaskul: None. M. Phelan: None. H. Wright: None.